Factors influencing the readiness to tackle the burden of ischaemic heart disease in India: a systematic review protocol - Dinesh Neupane; Shuvarthi Bhattacharjee; Nima Yaghmaei; Cao Tran Le Phuong (BMJ Open)
Introduction Ischaemic heart disease (IHD) is one of the leading causes of death and disease burden in India affecting all age groups. To reduce the deaths and tackle the burden of existing IHD, the government approach has been mostly through the National Health Policy (2017) and National Programme for Prevention and Control of Diabetes, Cardiovascular diseases and Stroke. This paper offers a protocol for the systematic review of studies exploring the factors influencing service readiness of the public health system of India to tackle the burden of IHD.Methods and analysis Electronic databases of Embase (Ovid), AMED (Ovid), HMIC (Ovid), BNI (ProQuest), CINAHL (EBSCO), EMCARE (Ovid), PsycINFO (ProQuest), MEDLINE/PubMed and Web of Science (Clarivate Analytics) will be searched till 2020 for primary studies. Grey literature will be accessed through OpenGrey, TRIP Medical, WHO database, MoHFW website, Open Government Data (OGD) Platform of India and Google Scholar (between 2010 and 2020). Primary studies meeting the eligibility criteria and grey literature published in English between 2010 and 2020 will be included. Data will be analysed through a conceptual framework, and the primary outcome will constitute both quantitative and qualitative data. The quality of included studies will be assessed based on study design. Data will be managed on the COVIDENCE platform. All authors will be involved in data extraction, quality appraisal, data synthesis and formulation of the final draft.Ethics and dissemination This study, being a systematic review, does not involve any clinical trial, primary data collection or empirical study involving humans or animals. Therefore, no ethical permissions were sought by reviewers.PROSPERO registration number CRD42020219490.